Linguistique et Colonialisme: petit traité de glottophagie - Calvet, Louis-Jean (1974)
This book deals with the relationships between linguistics and colonialism, focusing primarily on France and the francophone world. It outlines how, during the colonial era, relationships of linguistic difference were translated into relationships of ‘superiority’. This supposed ‘superiority’ was then used as a justification of the colonial enterprise, and to maintain colonizers’ languages after the independence of the colonies. Calvet also discusses how within France itself, regional and minority languages were subjected to linguistic imperialism as part of nation-building. He concludes by suggesting that in the neo-colonial era, “la francophonie” is a thinly-veiled vehicle for maintaining political and economic power in the former colonies.